2012
DOI: 10.1093/cercor/bhs377
|View full text |Cite
|
Sign up to set email alerts
|

Twelve Months of Active Musical Training in 8- to 10-Year-Old Children Enhances the Preattentive Processing of Syllabic Duration and Voice Onset Time

Abstract: Musical training has been shown to positively influence linguistic abilities. To follow the developmental dynamics of this transfer effect at the preattentive level, we conducted a longitudinal study over 2 school years with nonmusician children randomly assigned to music or to painting training. We recorded the mismatch negativity (MMN), a cortical correlate of preattentive mismatch detection, to syllables that differed in vowel frequency, vowel duration, and voice onset time (VOT), using a test-training-rete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
222
2
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 204 publications
(255 citation statements)
references
References 81 publications
(114 reference statements)
24
222
2
7
Order By: Relevance
“…linguistic pitch discrimination (Marques, Moreno, Castro & Besson, 2007;Lee & Hung, 2008;Cooper & Wang, 2012), segmental and tonal processing (Marie, Delogu, Lampis, Belardinelli & Besson, 2011), and congruous prosody discrimination (Wong, Skoe, Russo, Dees & Kraus, 2007). Similar studies were conducted with babies and children who received musical training before taking a language test in contrast with a control group (Magne, Schön & Besson, 2006;Forgeard, Schlaug, Norton, Rosam, Iyengar & Winner, 2008;Moreno, Marques, Santos, Castro & Besson, 2009;Chobert, Clément, Velay & Besson, 2012;François, Chobert, Besson & Schön, 2013). The results leave no doubt about the fact that music training brings about physical changes, especially regarding motor skills such as unimanual and bimanual responses, as well as cognitive and behavioural changes, e.g.…”
Section: Introductionsupporting
confidence: 58%
“…linguistic pitch discrimination (Marques, Moreno, Castro & Besson, 2007;Lee & Hung, 2008;Cooper & Wang, 2012), segmental and tonal processing (Marie, Delogu, Lampis, Belardinelli & Besson, 2011), and congruous prosody discrimination (Wong, Skoe, Russo, Dees & Kraus, 2007). Similar studies were conducted with babies and children who received musical training before taking a language test in contrast with a control group (Magne, Schön & Besson, 2006;Forgeard, Schlaug, Norton, Rosam, Iyengar & Winner, 2008;Moreno, Marques, Santos, Castro & Besson, 2009;Chobert, Clément, Velay & Besson, 2012;François, Chobert, Besson & Schön, 2013). The results leave no doubt about the fact that music training brings about physical changes, especially regarding motor skills such as unimanual and bimanual responses, as well as cognitive and behavioural changes, e.g.…”
Section: Introductionsupporting
confidence: 58%
“…There is strong evidence from previous cross-sectional studies comparing adult musicians and nonmusicians that long-term music training promotes brain plasticity (Münte, Altenmüller, & Jäncke, 2002) in modifying the functional (Schneider et al, 2002;Pantev et al, 1998) and structural (Elmer, Hänggi, Meyer, & Jäncke, 2013;Gaser & Schlaug, 2003;Schneider et al, 2002) architecture of the auditory pathway. Results of longitudinal studies, mostly in children, showed that music training can be the cause of the observed effects (François, Chobert, Besson, & Schön, 2013;Strait, Parbery-Clark, O'Connell, & Kraus, 2013;Chobert, François, Velay, & Besson, 2012;Moreno et al, 2011;Hyde et al, 2009;Moreno et al, 2009). Most importantly for the present purposes, there is also evidence that music training improves different aspects of speech processing (for review, see Asaridou & McQueen, 2013;Kraus & Chandrasekaran, 2010).…”
Section: Introductionmentioning
confidence: 81%
“…Because this task was more difficult for French native speakers than the other tasks, as revealed by behavioral data, the increased N100 may reflect increased focused attention (Strait et al, 2015) and mobilization of neuronal resources in musicians. An alternative but complementary interpretation is that this increase in N100 amplitude reflected increased neural synchronicity and structural connectivity in musicians, who are typically more sensitive to the acoustic-phonetic properties of speech sounds than nonmusicians who showed similar N100 components in all tasks (Bidelman et al, 2014;Elmer et al, 2013;Chobert et al, 2012;Musacchia et al, 2007;Wong & Perrachione, 2007).…”
Section: Cascading Effects From Perception To Word Learningmentioning
confidence: 99%
“…The effects of intense musical training on auditory processing have been well documented in various cross-sectional (Baumann et al, 2008;Meyer et al, 2006;Pantev et al, 1998; and longitudinal (Chobert, Francois, Velay, & Besson, 2012;Hyde et al, 2009;Moreno et al, 2009) studies. Currently, the intrinsic meaning of enhanced or reduced N1 amplitudes in musicians compared with nonmusicians is still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%